«Valentin et Orson», de Paris à Lyon (Carte Romanze, 2015)
Valentin et Orson fut publié d’abord à Lyon (1489, 1495), puis à Paris (ca 1511-1519). Le but de cet article est double: vérifier si le passage d’un centre éditorial à l’autre a impliqué une évolution du texte; montrer l’intérêt d’une collation systématique sur plusieurs éditions, même plus tardives, afin d’établir une édition critique.Valentin et Orson was first published in Lyon (1489, 1495), then in Paris (ca 1511-1519). This article has two aims: first, to establish whether the transfer from the former to the latter editorial centre brought with some kind of evolution of the text; second, to prove how interesting a systematic collation of many editions can be, in establishing a critical edition.